The Gradual Growth of the Mohist Core Philosophy: Tracing Fixed Formulations in the Mozi*. Issue 1 (2nd January 2016) - Defoort, Carine
Abstract : Because of the paucity of hard facts in our knowledge of early texts such as the Mozi, we inevitably have had to rely on assumptions when interpreting these texts. These assumptions have contributed to the portrayal of Mo Di as a philosopher, the founder of Mohist thought, and promoter of a coherent thought system in Ten Core Ideas. We can read the Mozi in a novel way by methodologically putting these assumptions on hold, not necessarily by rejecting them. This approach draws attention to the differences among the Ten Core Ideas, their not quite fixed forms, and their remarkably poor presence in the Mozi . It leads to another, equally plausible portrayal of Mohist thought as gradually shaped by its authors and editors along with the formation of the book.